Repeat treatment of acute hereditary angioedema attacks with open‐label icatibant in the FAST‐1 trial. (August 2014) - Malbrán, A.; Riedl, M.; Ritchie, B.; Smith, W. B.; Yang, W.; Banerji, A.; Hébert, J.; Gleich, G. J.; Hurewitz, D.; Jacobson, K. W.; Bernstein, J. A.; Khan, D. A.; et al.
Summary Hereditary angioedema (HAE) is characterized by potentially life‐threatening recurrent episodes of oedema. The open‐label extension (OLE) phase of the For Angioedema Subcutaneous Treatment (FAST)‐1 trial (NCT00097695) evaluated the efficacy and safety of repeated icatibant exposure in adults with multiple HAE attacks. Following completion of the randomized, controlled phase, patients could receive open‐label icatibant (30 mg subcutaneously) for subsequent attacks. The primary end‐point was time to onset of primary symptom relief, as assessed by visual analogue scale (VAS). Descriptive statistics were reported for cutaneous/abdominal attacks 1–10 treated in the OLE phase and individual laryngeal attacks. Post‐hoc analyses were conducted in patients with ≥ 5 attacks across the controlled and OLE phases. Safety was evaluated throughout. During the OLE phase, 72 patients received icatibant for 340 attacks. For cutaneous/abdominal attacks 1–10, the median time to onset of primary symptom relief was 1·0–2·0 h. For laryngeal attacks 1–12, patient‐assessed median time to initial symptom improvement was 0·3–1·2 h. Post‐hoc analyses showed the time to onset of symptom relief based on composite VAS was consistent across repeated treatments with icatibant. One injection of icatibant was sufficient to treat 88·2% of attacks; rescue medication was required in 5·3% of attacks. No icatibant‐related serious adverse events were reported. Icatibant provided consistent efficacy and was well tolerated for repeated treatment of HAE attacks.